Global research trends in sarcopenia: a bibliometric analysis of exercise and nutrition (2005–2025) - Zhang, Runqian; Wang, Jiaxin; Xi, Huijuan; Cheng, Yue; Han, Bei (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to evaluate the current research landscape, identify emerging areas of interest, and provide scientific insights for further research in exercise and nutrition for sarcopenia.MethodsA comprehensive bibliometric analysis was conducted using publications retrieved from the Web of Science Core Collection and SCOPUS between January 1, 2005 and January 1, 2025, focusing on exercise and nutritional interventions for sarcopenia. CiteSpace and VOSviewer were employed to visualize research trends through analysis of annual publications, keyword evolution, journal contributions, author networks, country/regional distributions, institutional collaborations, citation patterns, and high-frequency terminology.ResultsThe analysis included 886 publications demonstrating a consistent upward trajectory in annual output. Geographical shifts revealed a transition of research leadership from traditional centers in the United States and Europe to emerging Asian contributors, particularly China. High-frequency keywords analysis identified core concepts including “Skeletal Muscle” (Betweenness Centrality Degree, BCD 0.13), “Resistance Exercise” (BCD 0.11), and “Muscle Strength” (BCD 0.13), with nutritional components “Dietary Protein” (BCD 0.19), “Vitamin D” (BCD 0.14), and “Amino Acids” (BCD 0.18) forming distinct research clusters. Cluster analysis revealed five thematic domains: Protein Metabolism (Cluster 1), Body Composition Assessment (Cluster 2), Resistance Training Modalities (Cluster 3), Frailty Syndromes (Cluster 4), and Metabolic Regulation (Cluster 5). Temporal keyword evolution showed a paradigm shift from foundational terms (“human skeletal muscle”, “amino acids”) to clinical outcome measures (“gait speed,” “physical function,” “inflammation”) and mechanisms.ConclusionThe research trend in sarcopenia is currently shifting from symptoms to underlying mechanisms. Meanwhile, the focus of exercise and nutritional interventions for sarcopenia is moving toward addressing the disease burden and health management of multiple chronic diseases associated with sarcopenia.